Root Fractures in the Primary Teeth and Their Management: A Scoping Review - Enrico Spinas; Gianni Di Giorgio; Martina Salvatorina Murgia; Valentino Garau; Mara Pinna; Nicoletta Zerman (MDPI AG, 2022)
(1) Background: Traumatic dental injuries constitute a major global health problem. Primary deciduous teeth of the upper frontal group are frequently affected by trauma, especially at an early age. It is important to treat primary traumatic injuries because early tooth loss can lead to aesthetic and functional alterations. The most common injuries are extrusion, lateral luxation, and intrusion. Root fracture is a less common complication that can lead to tooth extraction if not properly diagnosed and managed. However, there are a lack of data regarding primary root fracture treatment. The literature was reviewed to study the current knowledge on the treatment of these injuries, and to propose an operative protocol based on the results obtained. (2) Methods: A literature search was performed on Web of Science, PubMed/MEDLINE, and SCOPUS. The research focused on the following features: age of the patient; localization of the root fracture and type of displacement suffered (intrusive, extrusive, or lateral); type of emergency treatment or diagnostic test performed and their compliance with IADT guidelines; follow-up duration. (2) Results: Only 8 articles fully met the inclusion criteria, with a total of 46 patients and 62 root fractures. Out of a total of 62 root fractures, regarding only upper incisors, the most common treatment was splinting (n = 39) for a period ranging from 3 weeks to 3 months (with an average of six weeks). No treatment was performed for 23 of the root fractures. The splinting performed in most of the included cases was semi-rigid, with the splint held in place using a composite resin material. An orthodontic splint using brackets and 0.5 mm stainless steel wire was used in only in one study. (4) Conclusions: We deduced that the root fracture of primary teeth is a rare traumatic dental injury that can cause numerous complications, such as eruptive problems in the permanent teeth. Correct radiological diagnosis, immediate repositioning and semi-rigid splinting could be conservative methods to prevent premature tooth loss in very young patients.